The Climate-forming role of the production process of the forests of Ukraine - Platon Tretyak; Nelia Lukianchuk; Hryhoriy Krynytskyy (Наукові праці Лісівничої академії наук України)
Forest vegetation plays a significant climate-regulating, oxygen-producing and moisture-producing function, which has not yet been sufficiently studied. Therefore, the aim of our study was an original calculation of the total values of the oxygen-production process and evaporation by forest vegetation using the example of forest and forest-steppe zones of the Western region of Ukraine. Our generalizations are based on the results of calculating the impact of forest vegetation phytomass growth on the quantitative indicators of this production process: carbon sequestration, oxygen production, water vapor transpiration and the consumption of thermal energy for this, as well as the corresponding air cooling due to evaporation. The source materials were official data on the area of forests and their annual increment within the model regions and Ukraine as a whole, as well as for comparison – in Poland, Germany and within Central and Eastern Europe.